2013
DOI: 10.1063/1.4799735
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced piezoelectric performance of (0.98-x)Bi(Sc3/4In1/4)O3-xPbTiO3-0.02Pb(Zn1/3Nb2/3)O3 ternary high temperature piezoelectric ceramics

Abstract: (0.98-x)Bi(Sc3/4In1/4)O3-xPbTiO3-0.02Pb(Zn1/3Nb2/3)O3 (BSI-PT-PZN) high temperature piezoelectric ceramics were prepared by traditional solid-state reaction method. Combining X-ray diffraction results with piezoelectric data, it was found that the morphotropic phase boundary (MPB) occurred at x = 0.575. The piezoelectric constant d33, curie temperature Tc, and electromechanical coupling factor kp of BIS-PT-PZN ceramics with MPB composition were 427 pC/N, 412 °C, and 0.51, respectively. Furthermore, the strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Piezoelectric ceramics with a Curie temperature ( T c ) higher than that of the conventional PZT have recently received a great deal of attention for application in sensors and actuators working at elevated temperatures, particularly, for aerospace and automotive industries . PbNb 2 O 6 (PN) is one of the most promising materials for piezoelectric devices working at elevated temperatures due to its much higher Curie temperature ( T c ≈ 570°C) than that of the conventional Pb(Zr,Ti)O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric ceramics with a Curie temperature ( T c ) higher than that of the conventional PZT have recently received a great deal of attention for application in sensors and actuators working at elevated temperatures, particularly, for aerospace and automotive industries . PbNb 2 O 6 (PN) is one of the most promising materials for piezoelectric devices working at elevated temperatures due to its much higher Curie temperature ( T c ≈ 570°C) than that of the conventional Pb(Zr,Ti)O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…(b). These results show that Fe‐doped 0.367BS–0.633PTF ceramics have potential applications in HT power devices because of their increased Curie temperatures as well as their relative high permittivity and piezoelectricity values …”
Section: Resultsmentioning
confidence: 71%
“…32 Figures 5(a) and 5(b) display the vibration velocity v o (rms value) as a function of the electric field (rms value) and temperature rise as a function of vibration velocity of Mnmodified BS-PT ceramics, respectively. 37 It is observed that the vibration velocity increases with both the electric field and Mn content. For the compositions with 3 and 4 mol% Mn content, the vibration velocity of Mn-modified BS-PT ceramics increases rapidly with the electric field initially, and then become nearly saturated with further increasing electric field.…”
Section: Important Materials Properties For Actuator Applicationsmentioning
confidence: 96%
“…Very recently, the piezoelectric parameters of BS-PT ceramics used for the design of actuators have been characterized, and several kinds of HT piezoelectric actuators with new working principle have been proposed in our group. [32][33][34][35][36][37] It has been found that these piezoelectric actuators work stably at the temperature as high as 200 C. In this paper, recent progress in HT piezoelectric ceramics and actuators based on BS-PT solid solutions are summarized.…”
Section: Introductionmentioning
confidence: 99%